2015
DOI: 10.5899/2015/cna-00231
|View full text |Cite
|
Sign up to set email alerts
|

Analytic approximate solution for some integral equations by optimal homotopy analysis transform method

Abstract: The main aim of this paper is to propose a new and simple algorithm namely homotopy analysis transform method (HATM), to obtain approximate analytical solutions of integral equations. Integral equation occurs in the mathematical modeling of several models in physics, astrophysics, solid mechanics and applied sciences. The numerical solutions obtained by proposed method indicate that the approach is easy to implement and computationally very attractive. Finally, several numerical examples are given to illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…where q ∈ [0, 1] is an embedding parameter and ϕ (x, t; q) is the real function of x, t, and q. By means of generalizing the traditional homotopy methods, Liao [18][19][20][21][22][23][24] constructed the zero order deformation equation:…”
Section: Basic Idea Of the Fractional Homotopy Analysis Transform Methods (Fhatm)mentioning
confidence: 99%
See 1 more Smart Citation
“…where q ∈ [0, 1] is an embedding parameter and ϕ (x, t; q) is the real function of x, t, and q. By means of generalizing the traditional homotopy methods, Liao [18][19][20][21][22][23][24] constructed the zero order deformation equation:…”
Section: Basic Idea Of the Fractional Homotopy Analysis Transform Methods (Fhatm)mentioning
confidence: 99%
“…The main aim of this article is to present analytical and approximate solution of fractional integro-differential equations by using new mathematical tool like homotopy analysis transform method. The proposed method is coupling of the homotopy analysis method HAM and Laplace transform method [21][22][23][24][25][26]. We have studied some of linear and nonlinear fractional integro-differential equations with the help of homotopy analysis transform method.…”
Section: Introductionmentioning
confidence: 99%
“…(3.12) is linear and thus can be easily solved, especially by means of symbolic computation software such as Mathematica, Maple, Matlab. Yabushita et al [29] and Mohamed S. Mohamed et al [30,31,32] applied the homotopy analysis method to nonlinear ODE's and suggested the so called optimization method to find out the optimal convergence control parameters by minimum of the square residual error integrated in the whole region having physical meaning. Their approach is based on the square residual error.…”
Section: The Optimal Homotopy Analysis Methods (Oham)mentioning
confidence: 99%
“…Also the inverse of local fractional derivative to of f (x) order α in interval [a, b] is defined by [30,31]…”
Section: Preliminaries and Notationsmentioning
confidence: 99%
“…Several robust methods have been used to solve the FDEs, the fractional differential equations and dynamic systems containing fractional derivatives. Some of the most important methods are Adomian's decomposition method [10][11][12], the exp-function method [13], He's variational iteration method [14,15], the fractional subequation method [16], the first integral method [17], the homotopy analysis method [18], the (G ′ /G)-expansion method [19], the homotopy perturbation method [20,21], the spectral methods [22], and the transform methods [23]. In [24], the authors presented two methods, which are the exp(−ϕðξÞ)-expansion method and the Kudryashov method.…”
Section: Introductionmentioning
confidence: 99%